2022
DOI: 10.1371/journal.pone.0268564
|View full text |Cite
|
Sign up to set email alerts
|

A one-step foraminoplasty via a large trephine in percutaneous endoscopic transforaminal discectomy for the treatment of lumbar disc herniation

Abstract: Background Transforaminal percutaneous endoscopic lumbar discectomy (PELD) is a widely used basic technique for lumbar disc herniation (LDH) with advantages including causing less trauma and fast recovery. The secure, efficient, and rapid enlargement of the intervertebral foramen is a key step in PELD procedures. However, the conventional multi-step trephine system for foraminoplasty involves complicated surgical procedures. In this study, we reported an improved one-step foraminoplasty via a large trephine wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…3 PELD, a minimally invasive spine surgery, has been a mainstream technique for lumbar disc herniation. 4 Some studies suggested a similar incidence of recurrence between PELD and open discectomy or microendoscopic discectomy (MED). [5][6][7] But others reported that PELD had a higher reoperation rate than open surgery.…”
Section: Introductionmentioning
confidence: 99%
“…3 PELD, a minimally invasive spine surgery, has been a mainstream technique for lumbar disc herniation. 4 Some studies suggested a similar incidence of recurrence between PELD and open discectomy or microendoscopic discectomy (MED). [5][6][7] But others reported that PELD had a higher reoperation rate than open surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Two mainly used tools to perform foraminoplasty including a uoroscopy-guided bone reamer or trephine have mainly described in previous studies. Bone reamer is less likely to destabilize the facet joint and cause the neural injury [3] , but the time-demanding procedure increases the risk of radiation exposure [4] ; Trephine is more e cient [5] and less radiation exposure [6] , but it tends to excise too much bone around the intervertebral foramen [7] , increasing the risk of lumbar instability and neural injury [8] . Therefore, it is important to nd a balance between the dose of X-ray exposure and the amount of bone resection while ensuring the effectiveness of foraminoplasty.…”
Section: Introductionmentioning
confidence: 99%